(untitled) (Research, Society and Development, 2021)
This article presents the study of Alzheimer’s disease, a chronic and degenerative pathology that compromises cognitive functions, which lead to neuropsychiatric disorders, as well as behavioral changes and how music therapy can improve the quality of life of the elderly. The aim of the construct is to investigate the effects of using music therapy applied in the treatment of Alzheimer’s disease in elderly people diagnosed with psychopathology, due to its beneficial action of the aforementioned therapy. This is a systematic review of bibliographic procedure and a qualitative approach. The data survey was carried out on the Capes, Pepsic and Scielo platforms, using the descriptors: Alzheimer’s Disease, Elderly, Elderly, Music and Music Therapy. The results show that music therapy, by acting on cognitive functions, is in fact a functional alternative therapy with strong therapeutic evidence capable of generating a better quality of life, since its application proved to be able to delay the symptoms of the disease, in addition to restructure memories that had been forgotten.